Conferencing and Presentation English for Young Academics - Guest, Michael (Springer Texts in Education, 2018)
This book discusses and demonstrates the types of English discourse used at academic conferences and offers guidance to prospective conference participants from multiple perspectives. It is a combination of research taken from numerous academic conferences attended and observations made by the author, based on well-established research methods in applied linguistics, as well as a guidebook aimed at students, ESP teachers, and young academics and professionals wishing to upgrade their skills to participate fruitfully in, and contribute to, academic conferences. It offers academic novices and non-native speakers of English in particular much that is new and practical, far beyond the realm of simple 'presentation tips'. It addresses various topics, such as chairing discussions, poster management, discussion sessions, the TED phenomenon, workshops, and the emerging field of English as a lingua franca. The style alternates between the accessible and practical, and the analysis of the linguistic categories underpinning the discourse: genre analysis, the nature of the specialist discourse community, features of academic spoken discourse, and the presentation as multimodal narrative are all explored. The book includes authentic samples of model speech discourse throughout, along with questions and exercises for deliberation or practice in each chapter.